Olsztyn, 27th May, 2013
University of Warmia and Mazury in Olsztyn
Faculty of Geodesy and Land Management
Department of Satellite Geodesy and Navigation
ESSAY
Elementary rotation matrices in 3D space.
Daria Bruniecka
Geodesy and Satellite Navigation
1st year M.Sc. studies
Elementary rotation matrices in 3D space
Generated by modulo function
Prove that and check relation
Ri−1(α)=RiT(α)=Ri(−α);i = 1, 2, 3
The elementary 3D rotation matrices are constructed to perform rotations individually about the three coordinate axes.
Rotation about z-axis (x, y, z = 1,2,3)
Z = Z’
- the angle of elementary rotation about z-axis
From Oxyz to Ox’y’z’ we have R3 (+)
From Ox’y’z’ to Oxyz we have R3 (-)
From above figure we have:
We calculate:
Therefore:
And
From the point of view of matrix calculations we have:
Analogical considerations give us:
Rotation about x-axis (x, y, z = 1,2,3)
X = X’
- the angle of elementary rotation about x-axis
From Oxyz to Ox’y’z’ we have R1 (+)
From Ox’y’z’ to Oxyz we have R1 (-)
From above figure we have:
We calculate:
Therefore:
And
The elementary rotation about x:
Analogical considerations give us:
Rotation about y-axis (x, y, z = 1,2,3)
Y = Y’
- the angle of elementary rotation about y-axis
From Oxyz to Ox’y’z’ we have R1 (+)
From Ox’y’z’ to Oxyz we have R1 (-)
From above figure we have:
We calculate:
And:
The elementary rotation about y:
Elementary rotation matrices in 3D space
Generated by modulo function
Common looking on elementary rotations:
Subroutine: (i, α, A3x3); i = 1, 2, 3 = x, y, z
MOD(A,P) computes the remainder of the division of A by P
j = mod(i, 3) + 1
k = mod(j, 3) + 1
$$\text{mod}\left( i,\ j \right) = i - \frac{i}{j}j\ \ \ \ \ \ \ \ i,j \in N$$
For i -th row
A (i,i)=1 A(i,j)=0 A(i,k)=0
For j -th row
A (j,i)=0 A(j,j)= A(j,k)=
For k-th row
A(k,i)=0 A(k,j)= -A(j,k) A(k,k)=A(j,j)
for x-azis:
i = 1
j = mod (1,3) + 1 = 2
k = mod (2,3) +1 = 3
For 1st (i) row:
For 2nd (j) row:
For 3rd (k) row:
for y-azis:
i = 2
j = mod (2,3) + 1 = 3
k = mod (3,3) +1 = 1
For 1st (k) row:
For 2nd (i) row:
For 3rd (j) row:
for z-azis:
i = 3
j = mod (3,3) + 1 = 1
k = mod (1,3) +1 = 2
For 1st (j) row:
For 2nd (k) row:
For 3rd (i) row:
Elementary rotation matrices in 3D space
Prove that and check relation
Ri−1(α)=RiT(α)=Ri(−α);i = 1, 2, 3
For i=1, x-axis:
R1(+β)=$\ \begin{bmatrix} 1 & 0 & 0 \\ 0 & \text{cosβ} & \text{sinβ} \\ 0 & - \text{sinβ} & \text{cosβ} \\ \end{bmatrix}$
The inverse matrix:
$$R_{1}^{- 1}(\beta) = \frac{1}{\det{R_{1}(\beta)}}M^{T}$$
det R1(+β) - determinant of a matrix
M - matrix of cofactors
det R1(+β)= $\left| \begin{matrix} 1 & 0 & 0 \\ 0 & \text{cosβ} & \text{sinβ} \\ 0 & - \text{sinβ} & \text{cosβ} \\ \end{matrix} \right|$= cos2β+ sin2β=1
M11=${( - 1)}^{2}\left| \begin{matrix} \text{co}\text{sβ} & \text{sinβ} \\ - sin\beta & \text{cosβ} \\ \end{matrix} \right|$= cos2β+ sin2β=1 M12=${( - 1)}^{3}\left| \begin{matrix} 0 & \text{sinβ} \\ 0 & \text{cosβ} \\ \end{matrix} \right|$=0 M13=${( - 1)}^{4}\left| \begin{matrix} 0 & \text{cosβ} \\ 0 & - sin\beta \\ \end{matrix} \right|$=0
M21=( − 1)3$\left| \begin{matrix} 0 & 0 \\ - sin\beta & \text{cosβ} \\ \end{matrix} \right|$=0 M22=(−1)4$\left| \begin{matrix} 1 & 0 \\ 0 & \text{cosβ} \\ \end{matrix} \right|$=cosβ M23=( − 1)5$\left| \begin{matrix} 1 & 0 \\ 0 & - sin\beta \\ \end{matrix} \right|$=sinβ
M31=${( - 1)}^{4}\left| \begin{matrix} 0 & 0 \\ \text{cosβ} & \text{sinβ} \\ \end{matrix} \right|$=0 M32=( − 1)5$\left| \begin{matrix} 1 & 0 \\ 0 & \text{sinβ} \\ \end{matrix} \right| = -$sinβ M33=${( - 1)}^{6}\left| \begin{matrix} 1 & 0 \\ 0 & \text{cosβ} \\ \end{matrix} \right|$=cosβ
M=$\ \begin{bmatrix} 1 & 0 & 0 \\ 0 & \text{cosβ} & \text{sinβ} \\ 0 & - \text{sinβ} & \text{cosβ} \\ \end{bmatrix}$
$$R_{1}^{- 1}\left( \beta \right) = \frac{1}{\det{R_{1}\left( \beta \right)}}M^{T} = \begin{bmatrix}
1 & 0 & 0 \\
0 & \text{cosβ} & - \text{sinβ} \\
0 & \text{sinβ} & \text{cosβ} \\
\end{bmatrix}$$
Transposed matrix is as follows:
$$R_{1}^{T}(\beta) = \ \begin{bmatrix}
1 & 0 & 0 \\
0 & \text{cosβ} & - \text{sinβ} \\
0 & \text{sinβ} & \text{cosβ} \\
\end{bmatrix}$$
It is known that:
sin(−β) = −sin(β) and cos(−β) = cos(β)
So:
$$R_{1}\left( - \beta \right) = \begin{bmatrix}
1 & 0 & 0 \\
0 & \text{cosβ} & - \text{sinβ} \\
0 & \text{sinβ} & \text{cosβ} \\
\end{bmatrix}$$
To sum up the proof:
R1−1(β)=R1T(β)=R1(−β)
For i=2, y-axis:
R2(γ)=$\begin{bmatrix} c\text{osγ} & 0 & - sin\gamma \\ 0 & 1 & 0 \\ \text{sinγ} & 0 & \text{cosγ} \\ \end{bmatrix}$
det R2(γ)=$\left| \begin{matrix} \text{cosγ} & 0 & - sin\gamma \\ 0 & 1 & 0 \\ \text{sinγ} & 0 & \text{cosγ} \\ \end{matrix} \right|$= cos2γ+ sin2γ=1
M11=$\left| \begin{matrix} 1 & 0 \\ 0 & \text{cosγ} \\ \end{matrix} \right|$= cosγ M12=$\left| \begin{matrix} 0 & 0 \\ \text{sinγ} & \text{cosγ} \\ \end{matrix} \right|$=0 M13=$\left| \begin{matrix} 0 & 1 \\ \text{sinγ} & 0 \\ \end{matrix} \right| = - sin\gamma$
M21=$\left| \begin{matrix} 0 & - sin\gamma \\ 0 & \text{cosγ} \\ \end{matrix} \right|$=0 M22=$\left| \begin{matrix} \text{cosγ} & - sin\gamma \\ \text{sinγ} & \text{cosγ} \\ \end{matrix} \right|$= 1 M23=$\left| \begin{matrix} \text{cosγ} & 0 \\ \text{sinγ} & 0 \\ \end{matrix} \right|$=0
M31=$\left| \begin{matrix} 0 & - sin\gamma \\ 1 & 0 \\ \end{matrix} \right| =$sinγ M32=$\left| \begin{matrix} \text{cosγ} & - sin\gamma \\ 0 & 0 \\ \end{matrix} \right|$=0 M33=$\left| \begin{matrix} \text{cosγ} & 0 \\ 0 & 1 \\ \end{matrix} \right|$=cosγ
M=$\begin{bmatrix} \text{cosγ} & 0 & - sin\gamma \\ 0 & 1 & 0 \\ \text{sinγ} & 0 & \text{cosγ} \\ \end{bmatrix}$
$$R_{2}^{- 1}\left( \gamma \right) = \frac{1}{\det{R_{2}\left( \gamma \right)}}M^{T} = \begin{bmatrix}
c\text{osγ} & 0 & \text{sinγ} \\
0 & 1 & 0 \\
- sin\gamma & 0 & \text{cosγ} \\
\end{bmatrix}$$
$$R_{2}^{T}\left( \gamma \right) = \begin{bmatrix}
\text{cosγ} & 0 & \text{sinγ} \\
0 & 1 & 0 \\
- sin\gamma & 0 & \text{cosγ} \\
\end{bmatrix}$$
$$R_{2}^{}\left( - \gamma \right) = \ \begin{bmatrix}
\text{cosγ} & 0 & \text{sinγ} \\
0 & 1 & 0 \\
- sin\gamma & 0 & \text{cosγ} \\
\end{bmatrix}$$
To sum up the proof:
R2−1(γ)=R2T(γ)=R2(−γ)
For i=3, z-axis:
R3(α)=$\begin{bmatrix} \text{cosα} & \text{sinα} & 0 \\ - sin\alpha & \text{cosα} & 0 \\ 0 & 0 & 1 \\ \end{bmatrix}$
Det R3(α)= $\left| \begin{matrix} \text{cosα} & \text{sinα} & 0 \\ - sin\alpha & \text{cosα} & 0 \\ 0 & 0 & 1 \\ \end{matrix} \right|$= cos2α+ sin2α=1
M11=$\left| \begin{matrix} \text{cosα} & 0 \\ 0 & 1 \\ \end{matrix} \right|$= cosα M12=(-1)3$\left| \begin{matrix} - sin\alpha & 0 \\ 0 & 1 \\ \end{matrix} \right| = sin\alpha$ M13=$\left| \begin{matrix} - sin\alpha & \text{cosα} \\ 0 & 0 \\ \end{matrix} \right|$=0
M21=(-1)3$\left| \begin{matrix} \text{sinα} & 0 \\ 0 & 1 \\ \end{matrix} \right| = - sin\alpha$ M22=$\left| \begin{matrix} \text{cosα} & 0 \\ 0 & 1 \\ \end{matrix} \right|$=cosα M23=$\left| \begin{matrix} \text{cosα} & \text{sinα} \\ 0 & 0 \\ \end{matrix} \right|$=0
M31=$\left| \begin{matrix} \text{sinα} & 0 \\ \text{cosα} & 0 \\ \end{matrix} \right|$=0 M32=$\left| \begin{matrix} \text{cosα} & 0 \\ - sin\alpha & 0 \\ \end{matrix} \right|$=0 M33=$\left| \begin{matrix} \text{cosα} & \text{sinα} \\ - sin\alpha & \text{cosα} \\ \end{matrix} \right|$= 1
M=$\begin{bmatrix} \text{cosα} & \text{sinα} & 0 \\ - sin\alpha & \text{cosα} & 0 \\ 0 & 0 & 1 \\ \end{bmatrix}$
$$R_{3}^{- 1}\left( \alpha \right) = \frac{1}{\det{R_{3}\left( \alpha \right)}}M^{T} = \begin{bmatrix}
\text{cosα} & - sin\alpha & 0 \\
\text{sinα} & \text{cosα} & 0 \\
0 & 0 & 1 \\
\end{bmatrix}$$
$$R_{3}^{T}\left( \alpha \right) = \begin{bmatrix}
\text{cosα} & - sin\alpha & 0 \\
\text{sinα} & \text{cosα} & 0 \\
0 & 0 & 1 \\
\end{bmatrix}$$
$$R_{3}^{}\left( - \alpha \right) = \ \begin{bmatrix}
\text{cosα} & - sin\alpha & 0 \\
\text{sinα} & \text{cosα} & 0 \\
0 & 0 & 1 \\
\end{bmatrix}$$
To sum up the proof:
R3−1(α)=R3T(α)=R3(−α)